1993
DOI: 10.1016/0735-1097(93)90429-5
|View full text |Cite
|
Sign up to set email alerts
|

Five-year angiographic follow-up of factors associated with progression of coronary artery disease in the Coronary Artery Surgery Study (CASS)

Abstract: Univariate and multivariate associations with lesion progression and occlusion included diabetes, lesion location, elevated cholesterol level, interval infarction and lesion morphology. These angiographic results, collected in a prospective trial, are consistent with known risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
145
2
17

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 316 publications
(176 citation statements)
references
References 17 publications
12
145
2
17
Order By: Relevance
“…These include a higher rate of native vessel disease progression in diabetes, 13 the impact of diabetes on endothelial function particularly in the coronary microvasculature, 16 diabetes-associated hypercoagulability, 17 and an independent myocardial factor. 18,19 However, we believe that a more likely explanation is the differential risk of death from noncardiac causes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include a higher rate of native vessel disease progression in diabetes, 13 the impact of diabetes on endothelial function particularly in the coronary microvasculature, 16 diabetes-associated hypercoagulability, 17 and an independent myocardial factor. 18,19 However, we believe that a more likely explanation is the differential risk of death from noncardiac causes.…”
Section: Discussionmentioning
confidence: 99%
“…Over the 44 years since the first coronary bypass operation, there have been several angiographic follow-up studies, but this is the first report with the primary objective of comparing graft patency in patients with and without diabetes. The Coronary Artery Surgery Study included an angiographic follow-up substudy, 13 but this analysis dealt primarily with the status of the native vessels (grafted and ungrafted) at 5 years after surgery. Graft status was not commented on.…”
Section: Discussionmentioning
confidence: 99%
“…Progression of nonbypassed segments was 18.6% at 5 years. 22 More recently, in a study of patients awaiting first PCI after diagnostic angiography, Kaski et al 23 found angiographic progression in 24% of patients at a median follow-up of 8 months and a 57% incidence of acute coronary events in those patients with lesion progression. Of those patients with stenoses Ͼ50%, culprit lesions progressed to a greater extent (28% of culprit lesions intended for angioplasty progressed) than did nonculprit lesions (9% progressed).…”
Section: Glaser Et Al Clinical Progression Of Incidental Lesionsmentioning
confidence: 99%
“…Так, по данным исследо-вания CASS, процент стенозирования артерии больше 70% говорит о значимости поражения коронарной ар-терии и необходимости ее реваскуляризации [12]. Veterans Administration (США) и Европейские иссле-довательские центры принимают гемодинамически значимым стенозирование коронарной артерии свы-ше 50% [13].…”
Section: стресс-эхокг в оценке коронарного русла при ибсunclassified